Comparing the 2, 2′‐Biphenylenedithiophosphinate Binding of Americium with Neodymium and Europium. (22nd September 2016) - Cross, Justin N.; Macor, Joseph A.; Bertke, Jeffery A.; Ferrier, Maryline G.; Girolami, Gregory S.; Kozimor, Stosh A.; Maassen, Joel R.; Scott, Brian L.; Shuh, David K.; Stein, Benjamin W.; Stieber, S. Chantal E.
Abstract: Advancing our understanding of the minor actinides (Am, Cm) versus lanthanides is key for developing advanced nuclear‐fuel cycles. Herein, we describe the preparation of (NBu4 )Am[S2 P( t Bu2 C12 H6 )]4 and two isomorphous lanthanide complexes, namely one with a similar ionic radius (i.e., Nd III ) and an isoelectronic one (Eu III ). The results include the first measurement of an Am−S bond length, with a mean value of 2.921(9) Å, by single‐crystal X‐ray diffraction. Comparison with the Eu III and Nd III complexes revealed subtle electronic differences between the complexes of Am III and the lanthanides.